An Error Analysis of Pakistani ESL Learners’ Written Manuscripts at University Level - Bibi Halima; Dr. Rasib Mahmood; Aqsa Atta; Nuzhat Nawaz (Journal of Management Practices, Humanities and Social Sciences, 2021)
Errors are the most common possibility in the ESL learning process and Error Analysis, a never ending venture, remains an ongoing area of research as long as people continue to learn second or foreign language. Similarly, the present study aims to diagnose learners' linguistic choices and it categorizes errors in order to study competence and performance of participants in target language. Corder's (1974) procedural method of error analysis is followed as theoretical framework; the present article analyzes the written manuscripts of Pakistani graduating ESL learners. The corpus consisted of data collected through 200 students’ written work from two different faculties i.e., Basic Sciences and Computer Science. Data is collected through purposive sampling technique from first year university students. The study identifies, classifies, and explains seven classes of errors as follow: lexical errors, syntactic errors, morphological errors, semantic errors, errors of articles, spelling errors and online language errors. Results show that learners are influenced by the patterns of their L1; consequently, they translate, borrow, and rely more on L1. It suggests that they may be familiar with the rules of the target language but due to lack of practice, they cannot perform well. Also, findings of the study confirm that spelling, articles, and online language errors are the most common. The study concludes with a suggestion to look for constructive pedagogical strategies to reduce the high frequency of these errors in ESL classrooms in Pakistani context. The present study may act as a feedback for students and a clue of modification in pedagogical methodologies and syllabus design for teachers.